Depression and HIV risks: Engaging older African American women in HIV prevention education through the church - Ebor, Megan T.; Jackson, Aurora P. (Frontiers in Reproductive Health, 2023)
This report describes the recruitment of a sample of older African American women to test the effectiveness of an educational HIV prevention intervention that sought to reduce depressive symptoms and thereby HIV risks in this population. The outreach venue is the Black church. A framework for maximizing response is suggested. Of 62 women who participated in two arms of the intervention, 29 were assigned randomly to a four-session discussion group (experimental condition) and 33 were assigned to a one-session informational group (control condition) focused on HIV prevention education. Between-within subjects analyses of variance showed that participation in the study was associated with a significant improvement in the women's psychological status, i.e., decreased depressive symptoms. This change in depressive symptoms was due in part to the experimental condition assignment. Implications for future HIV prevention interventions, research, and methods used to maximize the probability of response among older African American women are discussed.